Recent Advances in Fluorescent Silk Fibroin - Lee, Ok Joo; Sultan, Md. Tipu; Hong, Heesun; Lee, Young Jin; Lee, Ji Seung; Lee, Hanna; Kim, Soon Hee; Park, Chan Hum (Frontiers in Materials, 2020)
Silk is a natural macromolecular protein consisting of fibroin and sericin. Silk fibroin (SF), derived from Bombyx mori, is a representative fibrous protein that has been used mainly in fashion textiles and surgical sutures. Also, SF has been extensively applied as a potential biomaterial in a number of biomedical and biotechnological fields, as SF can be reconstituted in various forms through physical and chemical processes. In addition to direct use of SF with intrinsic structure and properties, there are many researchers attempt to insert more novel functional properties into SF, despite retaining its favorable natural characteristics. In recent years, fluorescent silk obtained through various methods, such as the genetic modification or dye feeding method, has been applied in a variety of medical fields. These functionalized silks have properties that can be applied to new and versatile fields more than currently existing fields such as drug delivery, monitoring surgical and wound healing processes. This review focuses on the preparation methods and the latest technological advances on the use of fluorescent SF materials, especially their biomedical applications.